Knowledge, Beliefs and Practices of University Students Regarding Testicular Cancer and Testicular Self-Examination - KADIOĞLU, HASİBE (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: Although seen rarely, testicular cancer remains to be a public health problem as it is the most common cancer type in males aged between 15 and 35 years. The aim of this study is to evaluate knowledge, beliefs and practices of male university students regarding testicular cancer and testicular self-examination. Methods: This descriptive study was conducted with 681 first-year university students between November and December 2016. The data were collected using a Descriptive Form, Testicular Cancer Questionnaire and the Champion's Health Belief Model Scale (HBMS). Results: It was found that 91% of the students had no previous knowledge on testicular cancer, 88.3% had never heard of Testicular Self-Examination (TSE). Most of the students stated that they obtained information on testicular cancer and TSE from the internet. Students were found to have moderate level of perceived benefit, susceptibility, barrier, motivation/seriousness and self-efficacy with respect to testicular cancer and TSE. Conclusion: As a result of this research, it was found that university students lacked sufficient knowledge on testicular cancer and TSE. In order to improve the level of knowledge on testicular cancer and TSE, health professionals may provide trainings at universities, awareness may be raised among university students through elective courses and information may be disseminated via mass media.
Keywords: Testicular neoplasms; men's health; students; PUBLIC AWARENESS; MEN